HF (High-Frequency) Channel Probe. - Basler,Roy P; Bentley,Philip B; Price,Gary H; Rino,Charles L; Rust,Denise K (1985)
An experiment in Greenland has measured the transfer characteristics for HF signals propagation through disturbed regions of the ionosphere. Transmissions over the 1-hop path from Narssarssuaq to Thule have suffered distortions in the range (propagation time) and Doppler domains on the order of hundreds of microseconds and tems of Hertz, respectively. A frequency-modulated continuous wave (FMCW) waveform was used for oblique sounding purposes, and a pseudorandom noise modulation with a 20-kHz bandwidth was used to measure range and Doppler spreads. Spaced receivers were used to measure azimuthal angle of arrival, and independent ionospheric diagnostic data for points along the path were provided by the incoherent-scatter radar at Sondre Stromfjord. The results were interpreted generally in terms of geophysical plasma dynamics, and also, in particular, in terms of scatter effects produced by high-velocity plasma irregularities encountered along the mean ray paths.